EXPLOITATION OF PALAEONTOLOGICAL AND HYDROGEOLOGICAL FEATURES FOR GEOTOURISM IN MESOPOTAMIA - OINOI, KASTORIA, NORTHERN GREECE - Kazakis, N.; Syrides, G.; Voudouris, K. (Bulletin of the Geological Society of Greece, 2016)
The aim of this study is to reveal the geological, paleontological and hydrogeological features of the surrounding area of Oinoi in municipality of Kastoria, Northern Greece. These features can attract visitors and develop geotourism in the area. Fossil mollusk shells (Pectinidae family, Pecten and Flabellipecten) were recognized in three fossiliferous sites. Additionally, the palaeontological features are supplemented by impressive alternations of sedimentary strata, cavities, springs, small natural waterfalls and lakes as well as a small dam. Three routes (the longest is 12.3 Km) were defined for the promotion of these features. The routes are suitable for walking, jogging, mountain biking, climbing, for students, elder people and adults. This is a preliminary approach, since further research in the wider area is needed, in order to include more existing natural features, as well as to create a comprehensive management plan and define the criteria for the proposal of the site as a Geopark.